EXTH-41. A NANOPARTICLE-BASED CANCER-SELECTIVE GENE TRANSFER STRATEGY FOR LOCALIZED THERAPY OF MALIGNANT HIGH GRADE GLIOMAS. (11th November 2019) - Rao, Divya; Phal, Ashish; Naga, Varun; Negron, Karina; Oh, Yumin; Hanes, Justin; Soo Suk, Jung
Abstract: Treatment for malignant high grade gliomas entails surgery, followed by chemotherapy and/or radiation. Despite the intensive care, there is a ~90% recurrence rate. This is attributed to suboptimal efficacy of treatments in tackling widespread cancer cells. We have previously developed nanoparticles that provide widespread therapeutic distribution both in healthy and tumor tissues, but are incapable of differentiating between them. This limitation applies to the current standard-of-care and state-of-the-art gene therapies. Here, we evaluate the efficacy of DNA nanoparticles carrying promoters that drive transgene expression specifically in tumor cells to achieve widespread yet cancer-selective gene transfer in high grade gliomas. To identify tumor-specific promoters, we used ELISA to confirm elevated expression of proteins previously reported to be upregulated in tumor tissue. We observed that expression of survivin in cancer cells was significantly greater than that of other cancer-rich proteins, exhibiting two orders of magnitude greater levels in rodent and human cancer cells compared to their respective healthy cells. Furthermore, the CMV promoter mediated similarly high expression in healthy cells, whereas the level achieved by the survivin promoter was significantly lower, if not negligible, suggesting its tumor specificity. Likewise, CMV-driven plasmids delivered into the brain by the nanoparticles mediated virtually identical volumetric distribution of transgene expression in both normal and tumor tissues in vivo . In contrast, nanoparticles carrying survivin-driven plasmids provided widespread transgene expression only in an orthotopically established tumor, but not healthy brain tissue. Additionally, we demonstrate therapeutic efficacy in an established brain tumor model using the DNA nanoparticles carrying survivin promoter-driven plasmids expressing a therapeutic protein. We identified survivin promoter as a lead TSP and confirmed its ability to mediate highly efficient and widespread but cancer-selective transgene expression with the aid of our nanoparticles uniquely designed to penetrate in healthy and tumor tissues.